A saúde do trabalhador e a duração do trabalho: os desafios do teletrabalho - Teixeira, Fernanda da Rocha (2017)
This paper analyzes the regulation of Teleworking and discusses hermeneutic mechanisms in order to guarantee the right to health and continuance of work, both constitutionally assured. Rigorous Fordist / Taylorist management systems have long coexisted along with techniques implemented by the Toyotist system of flexible production. Pari passu the global production and the process of automation have given rise to a class that lives off its work - a concept which is signed by Professor Ricardo Antunes - increasingly heterogeneous and far from the configuration of secure and regulated employment relations. The new configurations of work, especially within neoliberal systems, disrupt the structure of labor relations, hampering the structuring and representation of the unions, individualizing workers and deviating them from the productive structure, which generates a serious acknowledgment crisis. The network - to paraphrase the expression coined by Bauman - is in agreement with provisions agreed worldwide that warrant Human Rights to workers as a mechanism for world peace maintenance. In this scenario, it is sought to instigate reflection on matters regarding the Brazilian legal system - control of conventionality and constitutionality - in order to guarantee full protection to the working environment through the consideration of fundamental rights, based on the dignity of the human person as proportionality criteria, and setting as background the constitutional doctrine of free enterprise moderated by the social value of work.